Therapeutic potential of natural products in schistosomiasis-associated liver fibrosis - Liu, Cuiling; Fisher, David; Pronyuk, Khrystyna; Musabaev, Erkin; Thu Hien, Nguyen Thi; Dang, Yiping; Zhao, Lei (Frontiers in Pharmacology, 2024)
Schistosomiasis is a parasitic disease that endangers human health and social development. The granulomatous reaction of Schistosoma eggs in the liver is the main cause of hepatosplenomegaly and fibrotic lesions. Anti liver fibrosis therapy is crucial for patients with chronic schistosomiasis.Although Praziquantel is the only clinical drug used, it's limited in insecticide treatment and has a long-term large-scale use, which is forcing the search for cost-effective alternatives. Previous research has demonstrated that plant metabolites and extracts have effective therapeutic effects on liver fibrosis associated with schistosomiasis. This paper summarizes the mechanisms of action of metabolites and some plant extracts in alleviating schistosomiasis-associated liver fibrosis. The analysis was conducted using databases such as PubMed, Google Scholar, and China National Knowledge Infrastructure (CNKI) databases. Some plant metabolites and extracts ameliorate liver fibrosis by targeting multiple signaling pathways, including reducing inflammatory infiltration, oxidative stress, inhibiting alternate macrophage activation, suppressing hepatic stellate cell activation, and reducing worm egg load. Natural products improve liver fibrosis associated with schistosomiasis, but further research is needed to elucidate the effectiveness of natural products in treating liver fibrosis caused by schistosomiasis, as there is no reported data from clinical trials in the literature.